Analysis of Human Origins and Development in Modern Science as a Scientific Explanation for Strengthening Al-Qur'an Scientific Literacy - Haryanto , Sri; Jumini, Sri; Faraheen Abdul Rahman, Nur; Purnamasari, Ika; Ali Mustofa Kamal, Muhamad (Universitas Negeri Semarang, 2026)
This study explores the complex relationship between the Islamic perspective on human creation, as detailed in the Quran, and modern scientific understanding, particularly in embryology, genetics, and developmental biology. This research used a hermeneutic-phenomenological method, which juxtaposes the Quranic narrative of human creation, including the creation of Adam from clay and the subsequent development of humans from “nutfah” (sperm drops) through various embryonic stages, with contemporary scientific discoveries. Data analysis was carried out using QDA Miner software. The results of this research provide a comprehensive understanding and view of human creation while validating the contribution of modern science to understanding human origins and development. These findings show remarkable symmetry between the Quranic descriptions and modern scientific knowledge, highlighting stages such as “nutfah,” “alaqah” (blood clots), “mudghah” (chewed substance), bone development, and the covering of bones with flesh. This study not only underlines the suitability of religious narratives with scientific insights but also enriches the dialogue between science and religion to increase the scientific literacy of the Quran, and the values ​​of science education, such as integrative, critical, empirical, spiritual, ethical, and interdisciplinary, and has a major impact on the development of science.